PENGARUH MEKANISME GCG DAN PENGUNGKAPAN CSR TERHADAP KINERJA KEUANGAN - Djazilah, Rachma; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to examine the influence of good corporate governance mechanism and the disclosure of corporate social responsibility to the financial performance of the company which is reflected in the return on equity (ROE). This sample collection method in this research has been carried out by using purposive sampling in which the sample is collected by conducting selection based on certain criteria in accordance with what is determined by the researcher. Based on the sample collection method, 78 of 26 manufacturing companies which are listed in Indonesia Stock Exchange (IDX) over 3 periods from 2012 to 2014 have been selected as samples. The analysis method is quantitative which has been carried by using classic assumption test and multiple linear regressions analysis. The result of the research shows that one of the good corporate governance mechanisms is the proportion of the board of independent commissioner and institutional ownership has an influence to the financial performance which is reflected in the return on equity (ROE). Meanwhile, the variables i.e. audit-committee, managerial ownership and disclosure of corporate social responsibility (CSR) do not have any influence to the financial performance which is reflected in return on equity (ROE).Keywords: Good corporate governance, disclosure of corporate social responsibility, and financial performance.